THE ROLE OF THE BASELINES IN THE LAW OF THE SEA AND THE MARITIME DELIMITATION PROCESS BETWEEN PERU AND CHILE - Peruana de Derecho Internacional, Sociedad (2020)
This article develops the role of the baselines for the delimitation of the maritimespaces of the States, according to the UNCLOS, as well as its importance for Peru and forthe demand of its legitimate claims before the International Court of Justice in the maritimedispute with Chile.